Pengaruh Bussiness Risk, Company Growth, Size Terhadap Debt Policy Yang Dimediasi Tax Aggressiveness Pada Perusahaan (GEMA EKONOMI, 2023)
This study aims to determine the effect of business risk, company growth, company size on debt policy mediated by tax aggressiveness in mining companies listed on the Indonesia Stock Exchange (IDX). This study was designed with hypothesis testing. Data collection uses secondary data in the form of annual financial reports from mining companies during the 2017-2019 period. The sampling technique used purposive sampling and obtained a sample of 37 companies with 111 observations or observations. While the data analysis technique used in this study is panel data analysis with e-views. The results of this study indicate that business risk has no effect on tax aggressiveness, but has a significant effect on debt policy. Company growth has no effect on tax aggressiveness or debt policy. Firm size has a significant effect on tax aggressiveness and debt policy. Tax aggressiveness has no effect on debt policy. Tax aggressiveness does not have a full role in mediating the effect of business risk, company growth, and company size on debt policy.